2015
DOI: 10.1002/ajh.24016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epigenetic versus standard induction chemotherapy for newly diagnosed acute myeloid leukemia patients ≥60 years old

Abstract: Older patients with acute myeloid leukemia (AML) have poor outcomes with standard induction chemotherapy. We retrospectively reviewed our institute's experience with epigenetic (Epi) versus cytarabine-and anthracycline-based intensive chemotherapy (IC) as induction in newly diagnosed AML patients aged 60 years and older. One hundred sixty-seven patients (n 5 84, IC; n 5 83, Epi) were assessed; 69 patients received decitabine and 14 azacitidine. Baseline characteristics between the IC and Epi patient cohorts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…13 For this reason, we recently analyzed our own experience with intensive "7ϩ3"-based chemotherapy versus Dec or Aza treatment in 167 consecutive unselected AML patients Ն60 years of age at Roswell Park Cancer Institute. 34 Similarly to Quintas-Cardama, 13 we found that standard intensive chemotherapy resulted in 2-fold higher CR rates than hypomethylating therapy (43% vs 20%; p Ͻ .01). Although univariate analysis demonstrated longer overall survival after intensive versus hypomethylating therapy (10.7 vs 9.1 months; p ϭ .01), multivariate analysis highlighted no independent impact of treatment choice.…”
Section: Hypomethylating Therapymentioning
confidence: 80%
See 4 more Smart Citations
“…13 For this reason, we recently analyzed our own experience with intensive "7ϩ3"-based chemotherapy versus Dec or Aza treatment in 167 consecutive unselected AML patients Ն60 years of age at Roswell Park Cancer Institute. 34 Similarly to Quintas-Cardama, 13 we found that standard intensive chemotherapy resulted in 2-fold higher CR rates than hypomethylating therapy (43% vs 20%; p Ͻ .01). Although univariate analysis demonstrated longer overall survival after intensive versus hypomethylating therapy (10.7 vs 9.1 months; p ϭ .01), multivariate analysis highlighted no independent impact of treatment choice.…”
Section: Hypomethylating Therapymentioning
confidence: 80%
“…25 Recent studies suggest that, although hypomethylating therapy in AML patients results in lower CR rates (10%-20%) than conventional intensive chemotherapy, an additional 10%-30% of these individuals nevertheless exhibit evidence of some disease response or stabilization and have overall survival rates equivalent or superior to other conventional treatments. 13,26,34 Lastly, and perhaps most importantly, hypomethylating therapy was well tolerated over long periods of time in unfit elderly individuals, with fewer required hospital days and RBC and platelet transfusions. 35,36 To date, the question of which older patients with AML benefit from intensive versus hypomethylating therapy has been addressed only in retrospective analyses.…”
Section: Hypomethylating Therapymentioning
confidence: 99%
See 3 more Smart Citations